2011
DOI: 10.1111/j.1476-5381.2011.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate down-regulates vascular matrix metalloproteinases and ameliorates vascular dysfunction and remodelling in renovascular hypertension

Abstract: BACKGROUND AND PURPOSEMounting evidence implicates matrix metalloproteinase (MMP) in the vascular dysfunction and remodelling associated with hypertension. We tested the hypothesis that treatment with pyrrolidine dithiocarbamate (PDTC), which interferes with NF-kB-induced MMPs gene transcription, could exert antihypertensive effects, prevent MMP-2 and MMP-9 up-regulation, and protect against the functional alterations and vascular remodelling of two-kidney, one clip (2K1C) hypertension. EXPERIMENTAL APPROACHSh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
(82 reference statements)
5
29
0
4
Order By: Relevance
“…The rats in the 2K1C hypertension group were treated with water (2K1C vehicle) or PDTC (2K1C PDTC). The rats in sham-operated groups received water (sham vehicle) or the same dose of PDTC (Sham PDTC), which was given at 100 mg/kg/day by gavage [15], starting 2 weeks after the induction of 2K1C hypertension. PDTC treatment was maintained for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rats in the 2K1C hypertension group were treated with water (2K1C vehicle) or PDTC (2K1C PDTC). The rats in sham-operated groups received water (sham vehicle) or the same dose of PDTC (Sham PDTC), which was given at 100 mg/kg/day by gavage [15], starting 2 weeks after the induction of 2K1C hypertension. PDTC treatment was maintained for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, MMP-2 degrades intracellular proteins such as troponin-I [8], myosin light chain [9], a-actinin [10] and titin [11], thus contributing to cardiac dysfunction. Transgenic mice with increased MMP-2 expression in cardiomyocytes develop left and right ventricular enlargements and important cardiac dysfunction [12], whereas hearts from MMP-2 knockout mice have preserved cardiac function and morphology when submitted to pressure overload conditions [13,14].We have previously shown that hypertension-induced increases in vascular MMP activity can be down-regulated at transcriptional level by inhibiting nuclear factor kappaB (NFjB) with pyrrolidine dithiocarbamate (PDTC) [15]. However, while PTDC has been previously shown to reduce the progression of cardiac hypertrophy, an effect associated with inhibition of cardiac MMP-2 up-regulation [16], there is no study examining the cardiac benefits of treatment with PDTC in the 2-kidney, 1-clip (2K1C) hypertension model, which is clearly associated with enhanced MMP-2 cardiac expression and activity and left ventricular dysfunction/remodelling [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Pyrrolidine dithiocarbamate has been used in experimental models of hypertension, resulting in decreased vascular iNOS upregulation and an associated amelioration of NO-dependent vasorelaxation and vascular remodeling. 4 Thus, the association of pyrrolidine dithiocarbamate to antihypertensive therapy should be considered, because it represents a preventive way to inhibit iNOS expression and the vascular dysfunction associated with its activity. Although pyrrolidine dithiocarbamate was shown to be safe in different doses and routes of administration in preclinical studies, 5 additional data on its safety in humans as well as on the mechanisms involved in its beneficial vascular effects are warranted.…”
Section: Inducible Nitric Oxide Synthase Inhibition As a Target For Tmentioning
confidence: 99%
“…Following renal angioplasty plasma renin activity, plasma Ang II concentration, as well as serum malondialdehyde-modified lowdensity lipoprotein concentration and urinary 8-hydroxy-2'-deoxyguanosine excretion were decreased in these patients with RVH, verifying the involvement of oxidative stress in the ethiopathogenesis of RVH. Accordingly, several potent antioxidants were investigated to be used as antihypertensive agents and were shown to reduce blood pressure by improving baroreflex sensitivity, down-regulating vascular matrix metalloproteinases or scavenging the oxygen radicals that would inactivate vasodilatory action of nitric oxide (NO) (3,4,5). Similar to antioxidants, aerobic exercise training was shown to reduce oxidative stress and inflammation and to increase anti-oxidant defenses by enhancing the resistance against reactive oxygeninduced lipid peroxidation and DNA damage (6,7).Voluntary running exercise in spontaneously hypertensive rats was shown to reduce plasma renin activity and plasma renin concentration (8) and improve microcirculatory profile in different tissues (9,10), making exercise a recommended non-pharmacological treatment modality in hypertension (11,12).…”
Section: Introductionmentioning
confidence: 99%